Two case reports of the parasitism of Ophionyssus natricis (Gervais, 1844) (Mesostigmata: Macronyssidae) in captive Epicrates crassus (Cope) (Squamata: Boidae) in Brazil - Mello-Oliveira, Victor de Souza [UNESP]; Jacinavicius, Fernando de Castro; Andrade, Lívia de Oliveira [UNESP]; Siconelli, Márcio Junio Lima; Pereira, Fernanda Mara Aragão Macedo; Soares-Neto, Lauro Leite; Hippólito, Alícia Giolo; Hoppe, Estevam Guilherme Lux [UNESP]; Dowling, Ashley P. G.; Barros-Battesti, Darci Moraes [UNESP]; Bassini-Silva, Ricardo (Springer Nature, 2025)
There are more than 200 species of Macronyssidae parasitizing reptiles, birds, and mammals worldwide. While most species are found on wild animals, show some degree of geographic, and host group specificity, Ophionyssus natricis thrives on captive snakes and lizards and as a result of the pet trade, has a cosmopolitan distribution. In this study, we are providing new host records for this species for the state of São Paulo, as well as SEM images and the first partial sequences of Brazilian specimens.